Sosialisasi Pentingnya Menabung dengan Metode Kreatif pada Anak Usia Dini di TK Lilik dan TK Putra Anugrah 2 pada Kelurahan Air Dingin - Al-Muhtadeebillah, Hussein; Zerlina, Jannati; Fitriyah, Siti Nur; Anjani, Fanisa Adri; Sitohang, Benedikta Angel; Rahayu, Filla Sri; Daulay, Syahrani Ramadhanti; Faradillah, Adinda Putri; Septina, Annisa; N, Nurhayani; Oktariza, Tengku Fadilla (Yayasan Daarul Huda Kruengmane, 2025)
The saving culture in Indonesia remains relatively low, largely due to the lack of early financial literacy education. This article discusses the Saving Habits Socialization Program conducted by KKN MBKM students from University of Riau in Kelulahan Air Dingin, targeting kindergarten-aged children. The program aimed to instill saving habits through creative and participatory methods such as decorating piggy banks, coloring with colored sand, and educational games. The results showed a positive response from both children and teachers, with improved understanding of saving concepts and increased motivation to set aside pocket money. Despite challenges such as inconsistent saving behavior among children, the program successfully met its objectives and serves as a strategic first step in shaping financial awareness and responsible money habits from an early age. The sustainability of the program depends heavily on continued support from parents and schools.